(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study of literary theory within higher education encompasses various theoretical frameworks and critical perspectives that influence interpretation and the understanding of texts. This paper examines the principles of literary interpretation and the study of several key issues in literary theory, drawing a comparative analysis across different educational contexts. Through a review of various theoretical schools of thought, such as formalism, structuralism, post-structuralism, feminism, and postcolonialism, the study highlights how these approaches shape academic discourse and influence students’ analytical skills in literature departments. The research also identifies the challenges and opportunities presented by these theoretical approaches in modern higher education curricula. The paper concludes by offering suggestions for integrating these principles into a more cohesive framework for the study of literary texts.